A new direct current circuit breaker with current regeneration capability - Sanzad Lumen, S.M. (Institute of Advanced Engineering and Science, 2021)
Direct current (DC) power systems are becoming very popular due to better control ability and equipment reliability thanks to the continuous development of power electronics. A DC circuit breaker (DCCB) used for current interruption in a DC network is a major part of the system. It plays the vital role of isolating networks during fault clearing as well as during normal load switching. Breaking the DC current is a major challenge as it does not have any natural zero crossing points like the AC current has. In addition, energy stored in the network inductances during normal operation opposes the instantaneous current breaking. Hence, all the conventional DC circuit breaker topologies use lossy elements to dissipate this stored energy as heat during the current breaking operation. However, it is possible to store this energy and reuse it later by developing an improvised topology. In this paper, the prospects of energy recovery and reuse in DC circuit breakers have been studied, and a new topology with regenerative current breaking capability has been proposed. This new topology can feed the stored energy of the network back into the same network after breaking the current and thus can improve the overall system efficiency. Â© 2021, Institute of Advanced Engineering and Science. All rights reserved.